Relevansi dan Tantangan Penerapan Prinsip Ekonomi Syariah dalam Era Ekonomi Digital - M, Abdullah Aryasatya Putra; Sri Wigati; Akbar, Dilfikar; Wicaksana, Darel Hylmi (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract: The rapid development of the digital economy has brought significant changes in global financial and business transactions. In this context, the sharia economy offers an alternative system based on justice, transparency, and social welfare. This article aims to analyze the relevance of sharia economics in the digital economy as well as identify the main challenges of its implementation. This study uses a qualitative-descriptive approach with literature studies from scientific journals, regulations, and related industry reports. An analysis was carried out on sharia economic principles such as the prohibition of usury, maysir, gharar, and social justice in the digital context. The results of the study show that sharia principles have the potential to form a more ethical and inclusive digital ecosystem, for example through sharia fintech, digital sharia capital markets, and sharia blockchains. However, there are challenges in the form of regulatory limitations, difficulties in ensuring compliance of digital products with sharia, and low digital sharia financial literacy. This study recommends strengthening regulations, innovation of sharia-based financial products, and increasing public education to optimize the role of the sharia economy in the digital era. It is hoped that various parties, including the government, industry, and academia, can collaborate in creating a fair and sustainable digital economy ecosystem in accordance with sharia principles.Keywords: Sharia Economics, Digital Economy, Sharia Fintech, Sharia Blockchain, Sharia Financial Regulation. Abstrak: Perkembangan pesat ekonomi digital telah membawa perubahan signifikan dalam transaksi keuangan dan bisnis global. Dalam konteks ini, ekonomi syariah menawarkan sistem alternatif berbasis keadilan, transparansi, dan kesejahteraan sosial. Artikel ini bertujuan untuk menganalisis relevansi ekonomi syariah dalam ekonomi digital serta mengidentifikasi tantangan utama penerapannya. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan studi literatur dari jurnal ilmiah, regulasi, serta laporan industri terkait. Analisis dilakukan terhadap prinsip ekonomi syariah seperti larangan riba, maysir, gharar, dan keadilan sosial dalam konteks digital. Hasil penelitian menunjukkan bahwa prinsip syariah berpotensi membentuk ekosistem digital yang lebih etis dan inklusif, misalnya melalui fintech syariah, pasar modal syariah digital, dan blockchain syariah. Namun, terdapat tantangan berupa keterbatasan regulasi, kesulitan dalam memastikan kepatuhan produk digital terhadap syariah, serta rendahnya literasi keuangan syariah digital. Studi ini merekomendasikan penguatan regulasi, inovasi produk keuangan berbasis syariah, serta peningkatan edukasi masyarakat untuk mengoptimalkan peran ekonomi syariah di era digital. Diharapkan berbagai pihak, termasuk pemerintah, industri, dan akademisi, dapat berkolaborasi dalam menciptakan ekosistem ekonomi digital yang adil dan berkelanjutan sesuai prinsip syariah.Kata kunci: Ekonomi Syariah, Ekonomi Digital, Fintech Syariah, Blockchain Syariah, Regulasi Keuangan Syariah.